An exposition of the theory of natural selection - Pond, Raymond Haines (My University, 1898)
Introduction: The aim of this paper is mainly to clearly present the ideas ordinarily implied by the term Natural Selection. The various elements entering into the theory are so interdependent that a separate consideration of each and a systematic treatment of the subjects are different. An outline has however been kept in mind and a recapitulation is appended to summarize the main points. The environment of an organism is the total of conditions which affect it. Earth presents few … which do not support some form of life. This means that life itself may exist subject to nearly all the conditions which earth affords. While this is true of life itself it is not true of every living organism. Few are the forms which can thrive in either of the dramatically opposed environments. Observation indisputably verifies that each species cherishes an ideal environment. For each form of life there is a halutai the usultans of whose conditions is supremely adapted to the higher welfare of the organism.
Citation: Pond, Raymond Haines. An exposition of the theory of natural selection. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Natural Selection; Environment; Organism; Theses; Manuscripts (documents)